Penguatan Kompetensi SDM dalam Pengelolaan Pembangunan Infrastruktur Berbasis Swadaya Masyarakat - Farida Juwita; Husna Purnama; Maria Elina; Epi Parela (CV. Tripe Konsultan, 2025)
Community-based infrastructure development is a participatory approach that encourages active community involvement in the planning, implementation, and supervision of development. However, the success of this approach is highly dependent on the competence of the human resources involved. This community service activity aims to improve the technical and managerial competence of human resources in managing village-scale infrastructure development. The implementation methods include needs identification, simple construction technical training, project human resource management training, assistance in preparing the Budget Plan (RAB), and evaluation through pre-tests and post-tests. The results of the activity show an increase in participants' understanding of technical planning, quality control, labor management, and budget management transparency. This competency strengthening has resulted in increased effectiveness and quality of self-reliant development implementation. This activity has practical implications in the form of an integrated training model combining civil engineering and human resource management approaches that can be replicated in other regions to support participatory, accountable, and sustainable village development.